Expert System Identification Of Learning Patterns The VARK Method - Marlinda, Linda; Saputra, Dwiki; Indrarti, Wahyu (Politeknik Ganesha Medan, 2019)
Nowadays computers have been widely used by many people, both parents, children, and adolescents. Basically, they only follow technological progress. And it eventually led to progress in the field of science. On the other hand, the background of the need for the seriousness of parents in knowing the pattern of their children's learning style is the amount of potential free time that is not well utilized by children in the learning process. Plus the number of parents who do not support children in developing their own mindset. Or the learning atmosphere that is still not conducive. In line with the advancement of technology and science, parents should be able to easily find out the right pattern of children's learning styles, to make it easier for their children to develop their mindset and imagination in the world of learning. And one of them can be by using an expert system. The expert system for identifying patterns of children's learning styles is an expert system designed as a tool for parents to identify patterns of children's learning styles with a dynamic knowledge base. This knowledge is obtained from various sources, including research carried out by experts in their fields and books related to learning styles. The knowledge base is arranged in such a way into logic with several provisions including the vark method (visual, auditory, read, kinesthetic), in order to facilitate system performance in making conclusions. Drawing conclusions in this expert system use the certainty factor method. This expert system will display several questions as indicators of the characteristics of the child's learning style that are felt, then later arrive at the final question. In the final result, the expert system will display the types of characteristics of the child's learning style.